New Information and Communication Technologies for climate services: Evidence from farmers in Ada East District, Ghana - Rebecca Sarku; Famous Addi; Emmanuel M.N.A.N. Attoh (Climate Services)
How people respond to climate information service (CIS) depends on how information is designed and communicated. While the introduction of new information and communication technologies (ICTs) has improved the delivery of CIS, there are persistent usability challenges, especially among smallholder farmers. This study examined the usability of new ICTs in delivering CIS for farming in Ada East District, Ghana. The research addressed the question, how do smallholder farmers respond to CIS delivered through new ICTs, and what are the usability challenges of these technologies. Using data from document reviews, interviews, and focus group discussions, findings show that farmers predominantly rely on local or indigenous knowledge and traditional ICTs like radio and television for CIS, 7 New ICTs including: Website on weather information, Bulletin on social media: Facebook, WhatsApp weather forecast presented as a flyer, YouTube video on weather information, Short message service (SMS), Audio WhatsApp weather forecast and Weather apps were identified, providing daily, weekly and seasonal forecasts outlooks. However, the utilisation of these new ICTs is relatively limited. Only a few farmers were aware of the delivery of CIS through these new ICTs. Farmers with smartphones are mainly those who access daily and seasonal forecast outlooks using new ICTs, while face-to-face interactions remain the common mode for disseminating information among farmers. Although new ICTs offer forecasts, usability is influenced by the relevance and comprehension of the content, location success and time, typography, symbols and graphics, language clarity, feedback and interactivity and ability to use the new ICT tools. The findings of the study have implications for CIS developers and providers to incorporate design principles such as revision of text structure, font style and size, symbols, wording pattern and word counts. It shed light on the evolving landscape of CIS delivery in farming communities, where traditional methods coexist with emerging digital platforms and provided knowledge on the need to raise awareness on the use of new ICTs with CIS among farmers. Practical Implications of the research for policy makers and practitioners: The use of Information and Communication Technologies (ICTs) in Climate Information Services (CIS) offers a transformative approach to agricultural decision-making for farmers. This research identifies various new ICT platforms including Websites, Bulletin on social media: Facebook, WhatsApp weather forecast presented as a flyer, YouTube video on weather information, Short message service (SMS, Audio WhatsApp weather forecast and Weather apps, as key tools for delivering weather and climate forecasts to farmers. The findings have crucial implications for policymakers, businesses, and agricultural extension services, emphasising the role of ICTs in enhancing access to vital climate information for improved farming practices. Implications for Policy Makers: Policymakers should work towards standardising content and delivery methods of CIS across various ICT platforms to ensure consistency and reliability. This includes setting guidelines for accuracy, clarity, and comprehensibility of weather information. Furthermore, regulatory frameworks should be established to monitor and evaluate the performance of new ICT-based CIS providers, ensuring they meet the required standards and addressing issues of misinformation.Policies should encourage the development of user-friendly ICT platforms that cater to the diverse needs of farmers. This involves promoting the design of intuitive interfaces that are easy to navigate and available in local languages. Policy support for user-centred design can enhance the effectiveness of ICT-based CIS by making them more accessible and practical for end-users.Enabling feedback mechanisms within new ICT-based CIS can enhance their relevance and usability. Policy initiatives should support integrating interactive features in CIS platforms that allow farmers to provide feedback, ask questions, and seek clarifications. This could involve the development of mobile apps or platforms where farmers can communicate directly with meteorologists or agricultural experts.The varied use of platforms such as websites, social media, and mobile apps allows for tailored dissemination of CIS to different segments of the farming population. Policy interventions should ensure equitable access to these technologies across all regions, especially targeting under-served and rural areas. This could involve subsidising data costs or providing ICT training to farmers to bridge the digital divide.Investment in ICT infrastructure is essential to support the effective delivery of CIS. This includes enhancing internet connectivity in rural areas, promoting the adoption of smartphones, and improving mobile network coverage. Such infrastructural developments will facilitate farmers’ access to real-time weather updates and ensure the sustainability of new ICT-based CIS. Implications for Businesses: The emergence of new ICT-based CIS presents significant business opportunities for ICT, telecommunications, and software development companies. Businesses can innovate by developing and marketing new applications, platforms, and services tailored to the needs of farmers. For instance, creating localised weather apps or integrating CIS with agricultural management systems can provide value-added services to the farming community. Businesses can explore partnerships with CIS providers to sponsor or subsidise the delivery of weather information services to farmers. This can enhance brand visibility and corporate social responsibility (CSR) while supporting the agricultural sector. For instance, telecommunications companies can offer discounted data plans for accessing CIS or collaborate with the Ghana Meteorological Agency to disseminate free weather updates via short message service (SMS).The adoption of new ICTs in agriculture opens up new markets for businesses. Companies can target rural and farming communities with customised products and services such as affordable smartphones, data plans, or specialised apps for agricultural purposes. Market research and segmentation strategies can help businesses identify and cater to the specific needs of different farming segments. Implications for Agricultural Extension Services: Agricultural extension services should focus on training and capacity building to help farmers effectively use new ICTs to access CIS. This includes training sessions, workshops, and tutorials on using smartphones, navigating websites, subscribing to SMS services, and understanding weather forecasts. Building farmers’ digital literacy is crucial for maximising the benefits of ICT-based CIS.Agricultural extension services can modernise their practices by integrating new ICT-based CIS into their outreach programs. Extension agents can use mobile apps, social media, and other digital platforms to disseminate weather information, offer real-time advice, and engage with farmers more effectively. This approach can enhance the reach and impact of extension services, making them more responsive to the needs of farmers.To enhance the usability of CIS, agricultural extension services should ensure that weather information is localised and presented in a context relevant to farmers. This involves translating weather updates into local languages, using culturally appropriate symbols, and providing practical advice that farmers can apply directly to their agricultural activities.Agriculture extension services can facilitate the formation of community networks or groups that share weather information and CIS updates via ICT platforms like WhatsApp or Facebook. These networks can serve as support systems where farmers exchange information, share experiences, and discuss the implications of weather forecasts on their farming practices.Establishing a feedback loop is essential for the continuous improvement of new ICT-based CIS. Extension agents can collect feedback from farmers on the usability, accuracy, and relevance of the information provided through various ICT platforms. This feedback can be used to refine and enhance CIS, ensuring that it meets the evolving needs of the farming community. Conclusion: By recognising and addressing the unique challenges and opportunities presented in our research findings, stakeholders can enhance the accessibility, usability, and impact of weather information on farming practices. Together, these efforts can contribute to a more resilient and informed agricultural sector that is better equipped to navigate the complexities of climate variability and change.